Protein conformational changes affect the sodium triple‐quantum MR signal. (12th July 2020) - Kleimaier, Dennis; Schepkin, Victor; Hu, Ruomin; Schad, Lothar R.
Abstract : The aim of this study was to investigate possible sodium triple‐quantum (TQ) signal dependence on pH variation and protein unfolding which may happen in vivo. The model system, composed of bovine serum albumin (BSA), was investigated over a wide pH range of 0.70 to 13.05 and during urea‐induced unfolding. In both experimental series, the sodium and BSA concentration were kept constant so that TQ signal changes solely arose from an environmental change. The experiments were performed using unique potential to detect weak TQ signals by implementing a TQ time proportional phase increment pulse sequence. At a pH of 0.70, in which case the effect of the negatively charged groups was minimized, the minimum TQ percentage relative to single‐quantum of 1.34% ± 0.05% was found. An increase of the pH up to 13.05 resulted in an increase of the sodium TQ signal by 225%. Urea‐induced unfolding of BSA, without changes in pH, led to a smaller increase in the sodium TQ signal of up to 40%. The state of BSA unfolding was verified by fluorescence microscopy. Results of both experiments were well fitted by sigmoid functions. Both TQ signal increases were in agreement with an increase of the availability of negatively charged groups. The results point to vital contributions of the biochemical environment to the TQ MR signals. The sodium TQ signal in vivo could be a valuable biomarker of cell viability, and therefore possible effects of pH and protein unfolding need to be considered for a proper interpretation of changes in sodium TQ signals. Abstract : The possible range of sodium triple‐quantum (TQ) MR signal was evaluated in bovine serum albumin (BSA) solutions with pH values of 0.70‐13.05 and during urea‐induced protein unfolding. Availability of the negatively charged groups in BSA led to a 225% increase in the sodium TQ signal during pH variation and up to 40% during protein unfolding. The results provide an assessment of the environmental contributions to the sodium TQ MR signal during its possible in vivo applications as a biomarker.